ANALISIS PENERAPAN AKUNTANSI BIAYA LINGKUNGAN TERHADAP LABA PERUSAHAAN PT. BINTANG INTERNASIONAL KENDARI - Monalisa, Monalisa (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2022)
Implementation of environmental cost accounting is one form of concern for the environment of a company, because the environment contributes to the company. The purpose of this study was to determine and analyze the implementation of the environmental cost accounting of corporate profits as well as how companies disclose environmental costs in the financial statements. This research was conducted at PT. Bintang Internasional Kendari. This study is a descriptive qualitative research and in this study using secondary data. Based on the result of research at PT. Bintang Internasional Kendari obtained that the company has not maximized in implementation of environmental cost accounting. Company in recognizing the environmental costs (waste management costs) included as costs of outside efforts by the consideration that the cost incurred as a service fee for management or waste disposal, and the costs will affect the company profits.